2010
DOI: 10.1128/jvi.02118-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pathobiologic Characterization of Pandemic H1N1 2009 Influenza Viruses from a Naturally Infected Swine Herd

Abstract: Since its initial identification in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
113
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 30 publications
7
113
0
1
Order By: Relevance
“…Since then, several countries have identified this novel influenza virus in pigs (Howden et al 2009, Hofshagen et al 2009, Weingartl et al 2010, Pasma & Joseph 2010, Pereda et al 2010. Similar to what have been previously described, clinical signs in infected pigs were typical of an acute respiratory SIV disease, with pyrexia, cough, dyspnea and anorexia (Howden et al 2009, Pasma & Joseph 2010, Pereda et al 2010.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Since then, several countries have identified this novel influenza virus in pigs (Howden et al 2009, Hofshagen et al 2009, Weingartl et al 2010, Pasma & Joseph 2010, Pereda et al 2010. Similar to what have been previously described, clinical signs in infected pigs were typical of an acute respiratory SIV disease, with pyrexia, cough, dyspnea and anorexia (Howden et al 2009, Pasma & Joseph 2010, Pereda et al 2010.…”
Section: Discussionsupporting
confidence: 54%
“…Phylogenetic analyses of the 8 gene segments of the 2009 pH1N1 have shown that neither the 2009 pH1N1 nor closely related progenitor viral genes were present in U.S swine influenza viruses prior to 2009 ). In the outbreak described here, similar to what occurred in other countries (Howden et al 2009, Weingartl et al 2010, the detection of the pH1N1 in pigs occurred after the onset of pandemic influenza in humans. Moreover, the farm at Embrapa Swine and Poultry Research Center attends the biosecurity rules in relation to visits, shower and quarantine.…”
Section: Discussionsupporting
confidence: 52%
“…Weingartl et al (36) compared the properties of pdm H1N1 2009 strain from human with swine pdmlike H1N1 2009 Canadian isolate by experimental infection of pigs. They observed differences in virus recovery from the lower respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been announced by the World Health Organization (WHO) that the pandemic H1N1 influenza virus is now in the postpandemic period but is expected to become a recurrent seasonal influenza virus and circulate for some years (WHO; http://www.who.int/csr/disease/swineflu/en/). Additionally, pandemic H1N1/2009 influenza viruses were also frequently isolated from pigs (17)(18)(19) that were proposed to be "mixing vessels" for the reassortment of influenza viruses.…”
mentioning
confidence: 99%